The Effect Of Work Motivation And Work Environment On Employee Performance At Pt. Fore Coffee Bandung City (Case Study At PT. Fore Coffee Bandung City) - Muhammad Viqram Arya Basuki; Yelli Eka Sumadhinata (Cakrawala Repositori IMWI, 2023)
This study aims to analyze the effect of work motivation and work environment on employee performance at PT Fore Coffee in the city of Bandung. The sample in this study involved employees of PT. Fore Coffee in the city of Bandung, West Java. Data collection techniques by distributing questionnaires. In measuring research variables, a five-point Likert Scale is used, which will be filled in by respondents according to variable indicators. To manage the collected data in an effort to get answers to the main problems, the data analysis method used is SPSS software. The results of the study show that work motivation and work environment have a simultaneous and significant effect on employee performance